2003
DOI: 10.1046/j.1365-2133.2003.05300.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for modulation of human epidermal differentiation and remodelling by CD40

Abstract: As a whole, our findings provide evidence that CD40+ keratinocytes represent a poorly differentiated population, not actively engaged in the cell cycle, which under specific stimulation is committed towards terminal differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 36 publications
2
8
0
Order By: Relevance
“…An extra support for a role of B2R agonists in keratinocyte differentiation is our observation of moderated (pro)filaggrin expression following stimulation of subconfluent cells with LBK, a novel effect that has not been described before in human keratinocytes. Comparative control experiments carried out to activate CD40, a molecule associated to keratinocyte differentiation (Concha et al, 2003), confirmed that the response evoked by LBK was indeed moderated.…”
Section: Figuresupporting
confidence: 57%
See 2 more Smart Citations
“…An extra support for a role of B2R agonists in keratinocyte differentiation is our observation of moderated (pro)filaggrin expression following stimulation of subconfluent cells with LBK, a novel effect that has not been described before in human keratinocytes. Comparative control experiments carried out to activate CD40, a molecule associated to keratinocyte differentiation (Concha et al, 2003), confirmed that the response evoked by LBK was indeed moderated.…”
Section: Figuresupporting
confidence: 57%
“…Human keratinocyte culture Cultures were prepared as previously described (Concha et al, 2003). Briefly, skin pieces split cut with a keratome device were incubated for 1 h at 371C with 0.05% trypsin (Life Technologies, Rockville, Maryland) to obtain epidermal sheets that were then pooled in Hanks' balanced salt solution (Life Technologies) supplemented with 10% fetal bovine serum (Hyclone, Logan, Utah).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A limited number of in vitro studies on CD40 ligation of human primary IFNγ-stimulated ECs showed that these cells express ICAM-1 and secrete RANTES (CCL5), TNFα, IL-6, IL-8, and MCP-1 (CCL2) (Denfeld et al , 1996; Gaspari et al , 1996; Peguet-Navarro et al , 1997; Companjen et al , 2002; Pasch et al , 2004). In addition, there is evidence that CD40-activated ECs stop proliferating and start differentiating (Peguet-Navarro et al , 1997; Grousson et al , 2000; Concha et al , 2003; Villarroel Dorrego et al , 2006). However, the full spectrum of effects mediated by CD40 ligation on the response of ECs is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…CD40 expression and function has been described on a variety of cell types [4][5][6][7] , including neurons 8 . Activation of the CD40 pathway is well-known to promote proliferation, survival, differentiation and maturation in a variety of immune and other cell types [9][10][11][12][13][14][15][16][17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%